2016
DOI: 10.1016/j.scs.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of building-integrated green technologies: A review and case study on applications of Multi-Criteria Decision Making (MCDM) method

Abstract: Retrofitting existing buildings with appropriate green technologies is an important element of strategies to mitigate climate change. The selection of green technologies can be a challenging task, where multiple criteria exist and interrelate. However, it is still common for decisions to be based on a single criterion, such as energy efficiency or cost. This paper aims to evaluate the application of Multi-Criteria Decision Making (MCDM) methods to the selection of green technologies for retrofitting to existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(81 citation statements)
references
References 32 publications
(45 reference statements)
2
78
0
1
Order By: Relevance
“…It is based on the Analytic Hierarchy Process (AHP) method by Saaty [42]. Literature review revealed that AHP is a useful method for weighting sustainability indicators as: (1) AHP has the characteristics of a hierarchical structure, which is aligned with the structures of most sustainability frameworks and makes the process easy to comprehend for stakeholders; (2) is simple and flexible; (3) provides a consistent verification operation; and (4) this method can be used with both qualitative and quantitative data [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…It is based on the Analytic Hierarchy Process (AHP) method by Saaty [42]. Literature review revealed that AHP is a useful method for weighting sustainability indicators as: (1) AHP has the characteristics of a hierarchical structure, which is aligned with the structures of most sustainability frameworks and makes the process easy to comprehend for stakeholders; (2) is simple and flexible; (3) provides a consistent verification operation; and (4) this method can be used with both qualitative and quantitative data [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…Fewer applications were found in the construction management [101][102][103][104], retrofitting [57,[105][106][107], building maintenance [108][109][110] and location selection [111][112][113] application domains. The question of how one method is better suited than another to address a specific problem is constantly scrutinized by researches and practitioners.…”
Section: Detailed Analysis Of Articles Published In the Period Of 201mentioning
confidence: 99%
“…Keshavarz Ghorabaee et al [56] provided a broad overview of the application of MCDM methods in supply chains. Si et al [57] reviewed the application of MCDM methods for the assessment of green technologies. Decision-making for green building, sustainable design, and energy related problems were overviewed [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…Technology development, the emergence of new products/service [36,37,48,49] Emergence of low-carbon or low-energy materials [50,51] Higher requirement of design for adaptability and durability [51] Changing market requirements and customer needs [37,38,42,52] Policy instruments an legislation on SB, Energy codes and standards [31,41,43,53,54] Change in the competitive landscape, threat from competitors [35,42] Increased cost and innovation pressure [35] Environmental issues and awareness [42,43] Stakeholder involvement and collaboration [40,42,55] Economic needs [36,42] Social pressure (e.g., occupant wellbeing improvement and social reputation) [42,43,56] Change of industrial network and requirement [34,57] Energy security [49] Internal factor…”
Section: External Factormentioning
confidence: 99%